Growth Patterns of Small Manufacturing Firms Before Failure: Interconnections with Financial Ratios and Nonfinancial Variables (International Journal of Industrial Engineering and Management, 2015)
This study focuses on the pre-failure growth in total assets, debt and sales of bankrupted manufacturing firms. Based on a sample of 128 Estonian firms, it is shown that two distinct growth patterns can be outlined. When the first pattern shows a gradual decline, then the other characterizes a more eclectic growth behavior. Several classical financial ratios have significantly different values through the established two patterns. Managers’ characteristics do not vary among the established patterns. Article history: Received (02.12.2014); Revised (22.05.2015); Accepted (21.06.2015)
Keywords: bankruptcy; failure process; financial ratios; growth patterns; managers’ characteristics